2005
DOI: 10.1152/japplphysiol.00975.2004
|View full text |Cite
|
Sign up to set email alerts
|

Decreased intestinal polyp multiplicity is related to exercise mode and gender in ApcMin/+ mice

Abstract: Moderate-intensity treadmill running can alter male Apc(Min/+) mouse polyp formation. This purpose of this study was to examine whether exercise mode differentially affects Apc(Min/+) mouse intestinal polyp development in male and female mice. Male and female Apc(Min/+) mice were randomly assigned to control, treadmill (18 m/min; 60 min/day; 6 days/wk), or voluntary wheel running (24-h access) groups. Nine weeks of training decreased total intestinal polyps by 29% in male treadmill runners (66 +/- 9; P = 0.038… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
113
2
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(132 citation statements)
references
References 31 publications
14
113
2
3
Order By: Relevance
“…As reported previously (37,38), the number of adenomas increased along the proximal-distal axis of the small intestine in Apc Min/+ mice (proximal = 8.31±1.1, middle = 22.1±2.6, distal = 46.31±3.1; p<0.001), which was also seen in Apc Min/+ TcRδ -/-mice (proximal = 6.1±1.1, middle=12.37±4.7, distal=18±4.9; p<0.005) (Fig. 3B).…”
Section: Apcsupporting
confidence: 73%
“…As reported previously (37,38), the number of adenomas increased along the proximal-distal axis of the small intestine in Apc Min/+ mice (proximal = 8.31±1.1, middle = 22.1±2.6, distal = 46.31±3.1; p<0.001), which was also seen in Apc Min/+ TcRδ -/-mice (proximal = 6.1±1.1, middle=12.37±4.7, distal=18±4.9; p<0.005) (Fig. 3B).…”
Section: Apcsupporting
confidence: 73%
“…Min/ϩ mouse, a genetic model of colon cancer (39), there is a greater loss of gastrocnemius type IIb fiber cross-sectional area compared with type IIa fiber (8). This selectivity to wasting stimuli may be related to oxidative muscle fibers having an increased tolerance for systemic inflammation and metabolic alterations that occur with many wasting diseases (56).…”
Section: During the Development Of Cachexia In The Apcmentioning
confidence: 99%
“…We previously demonstrated that tumor bearing, weight-stable Apc Min/ϩ mice have similar gastrocnemius muscle citrate synthase activities and functional capacity related to distance run in voluntary activity wheels compared with wild-type (WT) mice. (39). The purpose of this study was to determine the relationship between muscle oxidative capacity and muscle mass loss in primarily red and white hindlimb muscles during the development of cancer cachexia in the Apc Min/ϩ mouse.…”
Section: Apcmentioning
confidence: 99%
“…B, plasma cytokine concentrations from male understanding this phenomenon. In other studies, increased plasma IL6 is coincident with cachexia in male APC min mice but not female APC min mice (25). It may be that CARD9 is functioning upstream of plasma IL6 in male APC min mice to enhance cachexia and reduce viability, potentially through Th17-cell induction.…”
Section: Discussionmentioning
confidence: 78%